Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
The integration of a lithium transition metal composite oxide with high Ni content and an Al-rich surface modification layer containing Ca addresses the capacity degradation issue in nonaqueous electrolyte secondary batteries, enhancing cycle stability and performance.
Patent Information
- Application Number
- JP2025003234
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-11-14
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium transition metal composite oxides with high Ni content used in nonaqueous electrolyte secondary batteries experience significant Li extraction during charging, leading to instability in the layered crystal structure and a decrease in battery capacity over charge/discharge cycles.
A positive electrode active material is developed, comprising a lithium transition metal composite oxide with at least 80 mol % Ni and Al, combined with a surface modification layer containing at least Ca. This configuration stabilizes the layered structure and suppresses electrolyte reactions, thereby maintaining battery capacity.
The proposed solution effectively improves the charge/discharge cycle characteristics of nonaqueous electrolyte secondary batteries, preventing capacity degradation and enhancing overall battery performance.
Smart Images

Figure 2025061139000003 
Figure 2025061139000001 
Figure 2025061139000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, lithium transition metal composite oxides with a high Ni content have been attracting attention as a positive electrode active material with high energy density. For example, Patent Document 1 describes a compound represented by the general formula Li x Ni y Co z M m and a BET specific surface area of 0.8 m or less. 2 / g or less.
[0003] Patent Document 2 discloses a positive electrode active material for a nonaqueous electrolyte secondary battery, which has an α-NaFeO2 structure, contains one or more transition metal elements selected from the group consisting of Mn, Ni, and Co, and has an alkaline earth metal and W present on the particle surface of a lithium transition metal composite oxide. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-100295 A [Patent Document 2] JP 2018-129221 A Summary of the Invention [Problem to be solved by the invention]
[0005] When a lithium transition metal composite oxide with a high Ni content is used as the positive electrode active material of a non-aqueous electrolyte secondary battery, the amount of Li extracted during charging is large, and there is a problem that the layered crystal structure is destroyed by repeated charging and discharging, and the capacity decreases. Note that the techniques disclosed in Patent Documents 1 and 2 still have room for improvement in terms of charge and discharge cycle characteristics.
[0006] A positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a lithium transition metal composite oxide containing at least 80 mol % or more of Ni and Al relative to the total number of moles of metal elements excluding Li, and a surface modification layer formed on the surfaces of primary particles of the lithium transition metal composite oxide and containing at least Ca.
[0007] A nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode containing the above-described positive electrode active material for nonaqueous electrolyte secondary batteries, a negative electrode, and a nonaqueous electrolyte.
[0008] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure contains a lithium transition metal composite oxide with a high Ni content, and can contribute to improving the charge-discharge cycle characteristics of the battery. According to the positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure, a high-capacity non-aqueous electrolyte secondary battery can be provided in which the decrease in battery capacity due to charging and discharging is suppressed. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The layered structure of the lithium transition metal composite oxide contained in the positive electrode active material contains a transition metal layer such as Ni, a Li layer, and an oxygen layer, and the charge and discharge reaction of the battery progresses as Li ions in the Li layer reversibly enter and exit. When a lithium transition metal composite oxide with a high Ni content is used, many Li ions are extracted from the Li layer during charging of the battery, which can cause the layered structure to become unstable. On the surface of the lithium transition metal composite oxide with an unstable layered structure, an altered layer is formed by reaction with the electrolyte. The altered layer is the starting point for further structural changes in the lithium transition metal composite oxide, so the battery capacity gradually decreases with charging and discharging.
[0011] Therefore, the present inventors have conducted intensive research to solve the above problems, and have found that a positive electrode active material having a surface modification layer containing Ca on the surface of a lithium transition metal composite oxide containing a predetermined amount of Al can suppress the reaction with the electrolyte on the surface while stabilizing the layered structure due to the synergistic effect of Al and Ca, thereby suppressing the decrease in battery capacity due to charging and discharging. Since Al does not change its oxidation number during charging and discharging, it is presumed that its inclusion in the transition metal layer stabilizes the structure of the transition metal layer. In addition, it is presumed that Ca suppresses the erosion of the surface modification layer by the electrolyte due to electronic interaction.
[0012] An example of an embodiment of a nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail below. A cylindrical battery in which a wound electrode body is housed in a cylindrical battery case will be exemplified below, but the electrode body is not limited to the wound type, and may be a laminate type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated one by one with a separator interposed therebetween. In addition, the battery case is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, or the like, or may be a battery case made of a laminate sheet including a metal layer and a resin layer.
[0013] Fig. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 according to an embodiment. As illustrated in Fig. 1, the nonaqueous electrolyte secondary battery 10 includes an electrode assembly 14, a nonaqueous electrolyte (not shown), and a battery case 15 that accommodates the electrode assembly 14 and the nonaqueous electrolyte. The electrode assembly 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. The battery case 15 includes a cylindrical outer can 16 with a bottom, and a sealing body 17 that closes the opening of the outer can 16.
[0014] The electrode body 14 is composed of a long positive electrode 11, a long negative electrode 12, two long separators 13, a positive electrode tab 20 joined to the positive electrode 11, and a negative electrode tab 21 joined to the negative electrode 12. The negative electrode 12 is formed to have a size slightly larger than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer in the longitudinal direction and width direction (short direction) than the positive electrode 11. The two separators 13 are formed to have a size at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example.
[0015] The nonaqueous electrolyte secondary battery 10 includes insulating plates 18, 19 disposed above and below the electrode body 14. In the example shown in Fig. 1, a positive electrode tab 20 attached to the positive electrode 11 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and a negative electrode tab 21 attached to the negative electrode 12 passes outside the insulating plate 19 and extends toward the bottom side of the outer can 16. The positive electrode tab 20 is connected to the lower surface of a bottom plate 23 of the sealing body 17 by welding or the like, and a cap 27 of the sealing body 17 electrically connected to the bottom plate 23 serves as a positive electrode terminal. The negative electrode tab 21 is connected to the inner bottom surface of the outer can 16 by welding or the like, and the outer can 16 serves as a negative electrode terminal.
[0016] The exterior can 16 is, for example, a cylindrical metal container with a bottom. A gasket 28 is provided between the exterior can 16 and the sealing body 17, and the internal space of the battery case 15 is sealed. The exterior can 16 has a grooved portion 22 that supports the sealing body 17 and is formed, for example, by pressing the side portion from the outside. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface.
[0017] The sealing body 17 has a structure in which a bottom plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, and the current path between the lower valve body 24 and the upper valve body 26 is interrupted. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0018] The positive electrode 11, negative electrode 12, separator 13, and nonaqueous electrolyte that constitute the nonaqueous electrolyte secondary battery 10, and in particular the positive electrode active material contained in the positive electrode mixture layer 31 that constitutes the positive electrode 11, will be described in detail below.
[0019] [Positive electrode] The positive electrode 11 has a positive electrode current collector 30 and a positive electrode composite layer 31 formed on both sides of the positive electrode current collector 30. For the positive electrode current collector 30, a foil of a metal, such as aluminum or an aluminum alloy, that is stable in the potential range of the positive electrode 11, or a film having the metal disposed on the surface layer, can be used. The positive electrode composite layer 31 contains a positive electrode active material, a conductive material, and a binder. The thickness of the positive electrode composite layer 31 is, for example, 10 μm to 150 μm on one side of the positive electrode current collector 30. The positive electrode 11 can be produced by applying a positive electrode slurry containing a positive electrode active material, a conductive material, a binder, and the like to the surface of the positive electrode current collector 30, drying the coating, and then compressing it to form the positive electrode composite layer 31 on both sides of the positive electrode current collector 30.
[0020] Examples of the conductive material contained in the positive electrode mixture layer 31 include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer 31 include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may be used in combination with carboxymethylcellulose (CMC) or a salt thereof, polyethylene oxide (PEO), or the like.
[0021] The positive electrode active material includes a lithium transition metal composite oxide and a surface modification layer formed on the surface of a primary particle of the lithium transition metal composite oxide and containing at least Ca. The lithium transition metal composite oxide contains at least 80 mol % of Ni and Al relative to the total number of moles of metal elements excluding Li. By making the Ni content relative to the total number of moles of metal elements excluding Li in the lithium transition metal composite oxide 80 mol % or more, a high-capacity battery can be obtained.
[0022] The content of Ni relative to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide is preferably 90 mol % or more. This allows a battery with a higher capacity to be obtained. On the other hand, if the content of Ni exceeds 96 mol % relative to the total number of moles of metal elements other than Li, the content of Al and Ca becomes too small, making it impossible to ensure the stability of the layered structure and surface structure of the lithium transition metal composite oxide.
[0023] The lithium transition metal composite oxide has a layered structure. Examples of the layered structure of the lithium transition metal composite oxide include a layered structure belonging to the space group R-3m and a layered structure belonging to the space group C2 / m. Among these, a layered structure belonging to the space group R-3m is preferred in terms of high capacity and stability of the crystal structure.
[0024] Lithium transition metal composite oxides are generally represented by the formula Li a Ni x Al y Co z M w O2-b (wherein 0.95 < a < 1.05, 0.8 ≤ x ≤ 0.96, 0 < y ≤ 0.10, 0 ≤ z ≤ 0.15, 0 ≤ w ≤ 0.1, 0 ≤ b < 0.05, x + y + z + w = 1, and M is at least one element selected from Mn, Fe, Ti, Si, Nb, Zr, Mo, and Zn). The composite oxide can be used. In addition, the positive electrode active material may contain a lithium transition metal composite oxide other than that represented by the above general formula, or other compounds, as long as the object of the present disclosure is not impaired. The molar fraction of the metal element contained in the entire particles of the lithium transition metal composite oxide can be measured by an inductively coupled plasma optical emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.
[0025] It is preferable that a, which represents the ratio of Li in the lithium transition metal composite oxide, satisfies 0.95 ≤ a < 1.05, and more preferably satisfies 0.97 ≤ a ≤ 1.03. When a is less than 0.95, the battery capacity may decrease compared to the case where a satisfies the above range. When a is 1.05 or more, more Li compound needs to be added compared to the case where a satisfies the above range, which may not be economical from the viewpoint of production cost.
[0026] It is preferable that y, which represents the content of Al with respect to the total molar number of the metal elements excluding Li in the lithium transition metal composite oxide, satisfies 0 < y ≤ 0.10, and more preferably satisfies 0.03 ≤ y ≤ 0.07. Since the oxidation number of Al does not change during charge and discharge, it is considered that the structure of the transition metal layer is stabilized by being contained in the transition metal layer. On the other hand, when y > 0.10, Al impurities are generated and the battery capacity decreases. Al may be uniformly dispersed in the layered structure of the lithium transition metal composite oxide, or may be present in a part of the layered structure.
[0027] Co and M (M is at least one element selected from Mn, Fe, Ti, Si, Nb, Zr, Mo, and Zn) are optional components. z and w, which indicate the contents of Co and M relative to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide, preferably satisfy 0≦z≦0.15 and 0≦w≦0.1, respectively. Since Co is expensive, it is preferable to suppress the content of Co from the viewpoint of production costs.
[0028] The lithium transition metal composite oxide is, for example, a secondary particle formed by agglomeration of a plurality of primary particles. The particle size of the primary particles constituting the secondary particle is, for example, 0.05 μm to 1 μm. The particle size of the primary particle is measured as the diameter of a circumscribed circle in a particle image observed by a scanning electron microscope (SEM). The surface modification layer exists on the surface of the primary particle. In other words, the surface modification layer exists on the surface of the secondary particle of the lithium transition metal composite oxide, or on the interface where the primary particles contact each other.
[0029] The lithium transition metal composite oxide is a particle having a volume-based median diameter (D50) of, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm, and particularly preferably 7 μm to 15 μm. D50 means a particle diameter at which the cumulative frequency is 50% from the smallest particle diameter in the volume-based particle size distribution, and is also called the median diameter. The particle size distribution of the lithium transition metal composite oxide can be measured using a laser diffraction type particle size distribution measuring device (e.g., MT3000II manufactured by Microtrack Bell Co., Ltd.) with water as a dispersion medium.
[0030] The lithium transition metal composite oxide has a surface layer present from the surface to the inside, and a main body present inside the surface layer. The thickness of the surface layer is, for example, 1 nm to 5 nm.
[0031] The thickness of the surface modification layer is, for example, 0.1 nm to 5 nm. Within this range, the reaction between the electrolyte and the surface of the lithium transition metal composite oxide is suppressed, and therefore the decrease in battery capacity due to charging and discharging can be suppressed.
[0032] The surface modification layer contains at least Ca. The surface modification layer may contain, for example, Ca or a compound containing Ca. Examples of the compound containing Ca include CaO, Ca(OH)2, and CaCO3.
[0033] The content of Ca relative to the total moles of metal elements excluding Li in the surface modification layer when the composition is analyzed by energy dispersive X-ray spectroscopy (TEM-EDX) can be 1.5 mol% to 20 mol%. In this range, the charge / discharge cycle characteristics of the battery can be further improved by the synergistic effect with Al. Here, the composition of the surface modification layer in the positive electrode active material, and the composition of the main body and surface layer of the lithium transition metal composite oxide can be measured by analyzing each part in the cross section of the primary particle of the positive electrode active material using TEM-EDX to measure the contents of Ni, Co, Al, M, and Ca. Note that since the surface modification layer is thinner than the spot diameter of the irradiated electron beam, the composition of the surface layer is influenced by the composition of the adjacent surface modification layer, and even if a trace amount of Ca is detected in the measurement result of the surface layer, it is considered that Ca is not actually present in the surface layer.
[0034] Furthermore, it is preferable that no peak derived from CaO is present in the X-ray diffraction pattern obtained by X-ray diffraction measurement of the lithium transition metal composite oxide. When CaO is contained to an extent that it can be detected by X-ray diffraction measurement, a decrease in charge / discharge capacity may occur. Here, the X-ray diffraction pattern is obtained by a powder X-ray diffraction method under the following conditions using, for example, a powder X-ray diffractometer (manufactured by Rigaku Corporation, product name "RINT-TTR", radiation source Cu-Kα).
[0035] Measurement range: 15-120° Scan speed: 4° / min Analysis range: 30-120° Background: B-spline Profile function: Split pseudo-Voigt function Constraint condition: Li(3a)+Ni(3a)=1 Ni(3a)+Ni(3b)=y (y is the Ni content in each element) ICSD No.:98-009-4814 The surface modification layer may further contain Al. In other words, the surface modification layer may further contain at least one selected from Al or a compound containing Al, and a compound containing Ca and Al. An example of the compound containing Al is Al2O3. Also, an example of the compound containing Ca and Al is CaAl2O4 and Ca3Al2O6. The surface modification layer may further contain Li.
[0036] The molar ratio of Al to Ni in the surface modification layer, as determined by composition analysis using energy dispersive X-ray spectroscopy (TEM-EDX), may be greater than the molar ratio of Al to Ni in the main body, which can further improve the charge-discharge cycle characteristics of the battery through a synergistic effect with Ca.
[0037] In addition, the molar ratio of Al to Ni in the surface modification layer, as determined by composition analysis using energy dispersive X-ray spectroscopy (TEM-EDX), is preferably at least twice the molar ratio of Al to Ni in the main body. Within this range, the charge-discharge cycle characteristics of the battery can be improved significantly.
[0038] Next, an example of a method for producing a positive electrode active material including a lithium transition metal composite oxide and a surface modification layer will be described.
[0039] The method for producing a positive electrode active material includes, for example, a first step of obtaining a composite oxide containing Ni, Al, and an arbitrary metal element, a second step of mixing the composite oxide obtained in the first step with a lithium compound to obtain a mixture, and a third step of firing the mixture. Each parameter of the composition and thickness of the surface layer and the surface modification layer in the finally obtained positive electrode active material is adjusted by controlling, for example, the mixing ratio of the raw materials in the second step, the firing temperature and time in the third step, etc.
[0040] In the first step, for example, while stirring a solution of a metal salt containing Ni, Al, and an arbitrary metal element (Co, Mn, Fe, etc.), an alkaline solution such as sodium hydroxide is dropped to adjust the pH to the alkaline side (e.g., 8.5 to 12.5), thereby precipitating (co-precipitating) a composite hydroxide containing Ni, Al, and the arbitrary metal element, and the composite hydroxide is calcined to obtain a composite oxide containing Ni, Al, and the arbitrary metal element. The calcination temperature is not particularly limited, but is, for example, in the range of 300°C to 600°C.
[0041] In the second step, the composite oxide obtained in the first step is mixed with a lithium compound and a calcium compound to obtain a mixture. Examples of the lithium compound include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. Examples of the calcium compound include Ca(OH)2, CaO, CaCO3, CaSO4, and Ca(NO3)2. The mixing ratio of the composite oxide obtained in the first step and the lithium compound is preferably such that, for example, the molar ratio of metal elements other than Li:Li is in the range of 1:0.98 to 1:1.1, in order to easily adjust each of the parameters to the ranges specified above. In addition, the mixing ratio of the composite oxide obtained in the first step and the calcium compound is preferably such that, for example, the molar ratio of metal elements other than Li:Ca is in the range of 1:0.0005 to 1:0.02, in order to easily adjust each of the parameters to the ranges specified above. In the second step, when the composite oxide obtained in the first step is mixed with the lithium compound and the calcium compound, other metal raw materials may be added as necessary. The other metal raw materials are oxides or the like containing metal elements other than the metal elements constituting the composite oxide obtained in the first step.
[0042] In the third step, the mixture obtained in the second step is fired at a predetermined temperature and time to obtain the positive electrode active material according to this embodiment. The firing of the mixture in the third step includes a multi-stage firing process including a first firing process in which the mixture is fired in a firing furnace under oxygen flow at a first heating rate to a first set temperature of 450°C to 680°C, and a second firing process in which the fired product obtained in the first firing process is fired in a firing furnace under oxygen flow at a second heating rate to a second set temperature of more than 680°C to 800°C. Here, the first heating rate is in the range of 1.5°C / min to 5.5°C / min, and the second heating rate is slower than the first heating rate and is in the range of 0.1°C / min to 3.5°C / min. By such multi-stage firing, the parameters of the composition and thickness of the surface layer and the surface modification layer in the finally obtained positive electrode active material of this embodiment can be adjusted to the above-specified range. The first heating rate and the second heating rate may be set in a plurality of rates for each temperature range, so long as they are within the ranges specified above. The holding time of the first set temperature in the first firing step is preferably 5 hours or less, more preferably 3 hours or less, in terms of adjusting each of the parameters of the lithium transition metal composite oxide to the ranges specified above. The holding time of the first set temperature is the time during which the first set temperature is maintained after the first set temperature is reached. The holding time of the second set temperature in the second firing step is preferably 1 hour to 10 hours, more preferably 1 hour to 5 hours, in terms of adjusting each of the parameters of the lithium transition metal composite oxide to the ranges specified above. The holding time of the second set temperature is the time during which the second set temperature is maintained after the second set temperature is reached. When firing the mixture, in terms of adjusting each of the parameters to the ranges specified above, the firing is performed, for example, in an oxygen stream with an oxygen concentration of 60% or more, and the flow rate of the oxygen stream is set to 10 cm / s of the firing furnace. 3 The flow rate can be in the range of 0.2 mL / min to 4 mL / min per kg of mixture and 0.3 L / min or more per kg of mixture.
[0043] The molar fraction of the metal element contained in the positive electrode active material obtained above was measured by inductively coupled plasma (ICP) emission spectrometry and was expressed by the general formula Li a Ni x Al y Co z M w Caα O 2-b (wherein 0.95 < a < 1.05, 0.8 ≤ x ≤ 0.96, 0 < y ≤ 0.10, 0 ≤ z ≤ 0.15, 0 ≤ w ≤ 0.1, 0.0005 ≤ α ≤ 0.02, 0 ≤ b < 0.05, x + y + z + w = 1, and M is at least one element selected from Mn, Fe, Ti, Si, Nb, Zr, Mo, and Zn). Note that Ca is not dissolved in the lithium transition metal composite oxide but is contained in the surface modification layer present on the surface of the lithium transition metal composite oxide. Also, a part of Al may be contained in the surface modification layer.
[0044] [Negative electrode] The negative electrode 12 has a negative electrode current collector 40 and a negative electrode composite layer 41 formed on both surfaces of the negative electrode current collector 40. As the negative electrode current collector 40, a foil of a metal stable within the potential range of the negative electrode 12 such as copper or a copper alloy, or a film having such a metal disposed on the surface layer can be used. The negative electrode composite layer 41 contains a negative electrode active material and a binder. The thickness of the negative electrode composite layer 41 is, for example, 10 μm to 150 μm on one side of the negative electrode current collector 40. The negative electrode 12 can be manufactured by applying a negative electrode composite slurry containing a negative electrode active material, a binder, etc. to the surface of the negative electrode current collector 40, drying the coating film, and then rolling to form the negative electrode composite layer 41 on both surfaces of the negative electrode current collector 40.
[0045] The negative electrode active material contained in the negative electrode composite layer 41 is not particularly limited as long as it can reversibly occlude and release lithium ions. Generally, carbon materials such as graphite are used. The graphite may be any of natural graphite such as flake graphite, massive graphite, and earthy graphite, artificial massive graphite, and artificial graphite such as graphitized mesophase carbon microbeads. Also, as the negative electrode active material, metals that alloy with Li such as Si and Sn, metal compounds containing Si, Sn, etc., and lithium titanium composite oxides may be used. Further, those provided with a carbon coating may be used. For example, SiO x (0.5 ≤ x ≤ 1.6), or Li 2y SiO (2+y) (0 < y < 2), a Si-containing compound in which fine particles of Si are dispersed in a lithium silicate phase, etc. may be used in combination with graphite.
[0046] The binder contained in the negative electrode mixture layer 41 may be a fluorine-containing resin such as PTFE or PVdF, PAN, polyimide, acrylic resin, polyolefin, or the like, as in the case of the positive electrode 11, but is preferably styrene-butadiene rubber (SBR). The negative electrode mixture layer 41 may also contain CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), or the like.
[0047] [Separator] For example, a porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably a polyolefin such as polyethylene or polypropylene, or cellulose. The separator 13 may have a single-layer structure or a laminated structure. In addition, a highly heat-resistant resin layer such as an aramid resin, or a filler layer containing an inorganic compound filler may be provided on the surface of the separator 13.
[0048] [Non-aqueous electrolyte] The non-aqueous electrolyte includes, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more of these can be used as the non-aqueous solvent. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine. Examples of the halogen-substituted product include fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, and fluorinated chain carboxylates such as methyl fluoropropionate (FMP).
[0049] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP).
[0050] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, and the like. and chain ethers such as ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0051] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more}, and imide salts such as these may be mentioned. The lithium salt may be used alone or in combination of two or more. Among these, from the viewpoints of ionic conductivity, electrochemical stability, etc., it is preferable to use LiPF6. The concentration of the lithium salt is, for example, 0.8 mol to 1.8 mol per 1 L of the non-aqueous solvent. Further, vinylene carbonate or a propane sultone-based additive may be added.
Example
[0052] Hereinafter, the present disclosure will be further described with reference to Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.
[0053] [Preparation of positive electrode active material] <Example 1> General formula Ni 0.90 Co 0.05 Al 0.05 O2, the metal composite oxide and calcium hydroxide (Ca(OH)2) were mixed so that the content of Ca was 0.1 mol% with respect to the total amount of Ni, Co, and Al, and further, lithium hydroxide monohydrate (LiOH·H2O) was mixed so that the molar ratio of the total amount of Ni, Co, Al, and Ca to Li was 1:1.02. The mixture was calcined from room temperature to 650 °C at a heating rate of 2 °C / min under an oxygen stream with an oxygen concentration of 95% (flow rate of 10 L / min per 1 kg of the mixture), and then from 650 °C to 720 °C at a heating rate of 1 °C / min. The calcined product was washed with water to remove impurities, and the positive electrode active material of Example 1 was obtained. As a result of analyzing the composition of the positive electrode active material of Example 1 by ICP-AES, Li 0.99Ni 0.899 Co 0.05 Al 0.05 Ca 0.001 It was O2.
[0054] <Example 2> General formula Ni 0.90 Co 0.05 Al 0.05 The positive electrode active material of Example 2 was obtained in the same manner as in Example 1, except that the metal composite oxide and calcium hydroxide (Ca(OH)2) were mixed so that the Ca content was 0.15 mol% relative to the total amount of Ni, Co, and Al in the metal composite oxide represented by O2. 0.99 Ni 0.899 Co 0.05 Al 0.05 Ca 0.0015 It was O2.
[0055] <Comparative Example> A positive electrode active material was obtained in the same manner as in Example 1, except that calcium hydroxide (Ca(OH)2) was not mixed, and the material was fired from room temperature to 650°C at a heating rate of 3.0°C / min, and then fired from 650°C to 720°C at a heating rate of 1°C / min. The composition of the positive electrode active material obtained was Li 0.99 Ni 0.90 Co 0.05 Al 0.05 O2. This was used as the positive electrode active material of the comparative example. In addition, 0.01 mol% of Ca was detected from the comparative example. This amount of Ca is very small compared to the Ca contained in Examples 1 and 2, so it is considered that there is no effect on the experimental results.
[0056] TEM-EDX measurement was performed on the positive electrode active materials of Examples 1 and 2 and Comparative Example, and composition analysis was performed on the main body and surface layer of the lithium transition metal composite oxide, and the surface modification layer. The main body was measured at an internal position 15 nm or more away from the surface of the lithium transition metal composite oxide. For Examples 1 and 2, measurements were performed at two different points, the first observation point and the second observation point. The results are shown in Table 1. The mole percentages of Ni, Co, and Al in Table 1 are listed with the total of Ni, Co, and Al being 100. Note that X-ray diffraction measurement was performed on Examples 1 and 2 and Comparative Example, but no peaks derived from CaO were present in the X-ray diffraction patterns for any of them.
[0057] [Table 1]
[0058] Although a small amount of Ca was detected in the surface layer at the second measurement point in Example 1 and the first and second measurement points in Example 2, as described above, it is believed that Ca is not actually present in the surface layer. The presence of Ca was also confirmed only in the surface modification layer by a separate electron energy loss spectroscopy (TEM-EELS). In other words, in Examples 1 and 2, Ca was present only in the surface modification layer. On the other hand, in the comparative example in which Ca was not added, Ca was not detected in any part. Also, in Examples 1 and 2, the Al content was highest in the surface modification layer, followed by the surface layer and the main body. On the other hand, in the comparative example, the Al content was approximately the same in all parts.
[0059] Next, test cells were fabricated as follows using the positive electrode active materials of Examples 1 and 2 and the Comparative Example.
[0060] [Preparation of positive electrode] The positive electrode active material of Examples 1 and 2 and Comparative Example was mixed in a ratio of 95 parts by mass, 3 parts by mass of acetylene black as a conductive material, and 2 parts by mass of polyvinylidene fluoride as a binder, and this was mixed with N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. Next, the slurry was applied to a positive electrode current collector made of aluminum foil with a thickness of 15 μm, and after drying the coating film, the coating film was rolled with a rolling roller and cut into a predetermined electrode size to obtain a positive electrode in which a positive electrode composite layer was formed on both sides of the positive electrode core. In addition, an exposed portion in which the surface of the positive electrode core was exposed was provided in a part of the positive electrode. Positive electrodes were prepared in the same manner in other Examples and Comparative Examples.
[0061] [Preparation of negative electrode] Natural graphite was used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode composite slurry. The negative electrode composite slurry was applied to both sides of a negative electrode core made of copper foil, and the coating film was dried. The coating film was then rolled using a rolling roller and cut to a predetermined electrode size to obtain a negative electrode in which a negative electrode composite layer was formed on both sides of the negative electrode core. An exposed portion was provided in part of the negative electrode, where the surface of the negative electrode core was exposed.
[0062] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.
[0063] [Preparation of test cell] An aluminum lead was attached to the exposed part of the positive electrode containing the positive electrode active material of Examples 1 and 2 and Comparative Example, and a nickel lead was attached to the exposed part of the negative electrode, and the positive electrode and the negative electrode were spirally wound with a polyolefin separator interposed therebetween, and then pressed in the radial direction to produce a flat wound electrode body. This electrode body was placed in an exterior body, and the nonaqueous electrolyte was injected, and the opening of the exterior body was sealed to obtain a test cell.
[0064] [Evaluation of capacity retention rate] The following cycle test was carried out on the batteries prepared by incorporating the positive electrodes containing the positive electrode active materials of Examples 1 and 2 and Comparative Example. The discharge capacity at the first cycle and the discharge capacity at the 30th cycle of the cycle test were obtained, and the capacity retention rate was calculated by the following formula.
[0065] Capacity retention rate (%) = (30th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100 <Cycle test> The test cell was charged at a constant current of 0.2 It in a temperature environment of 25°C until the battery voltage reached 4.2 V, and then charged at a constant voltage until the current value reached 1 / 100 It at 4.2 V. Then, the test cell was discharged at a constant current of 0.2 It until the battery voltage reached 2.5 V. This charge / discharge cycle was repeated 30 times.
[0066] The capacity retention rates of Examples 1 and 2 and the Comparative Example are shown in Table 2. The capacity retention rates of the test cells of Examples 1 and 2 shown in Table 2 are shown relatively to the capacity retention rate of the test cell of Comparative Example 1, which is set to 100%.
[0067] [Table 2]
[0068] As shown in Table 2, Examples 1 and 2, in which a positive electrode active material containing Ca in the surface modification layer was used, had a higher capacity retention rate than the Comparative Example, in which a positive electrode active material not containing Ca in the surface modification layer was used. [Explanation of symbols]
[0069] 10 Nonaqueous electrolyte secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 15 Battery case 16 Outer can 17 Sealing body 18,19 Insulating plate 20 Positive tab 21 Negative electrode tab 22 Grooved part 23 Bottom plate 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket 30 Positive electrode current collector 31 Positive electrode mixture layer 40 Negative electrode current collector 41 Negative electrode composite layer
Claims
1. a lithium transition metal composite oxide containing at least 80 mol % or more of Ni and Al relative to the total number of moles of metal elements excluding Li; a surface modification layer containing at least Ca and formed on the surfaces of primary particles of the lithium transition metal composite oxide.
2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the surface modification layer further contains Al.
3. The lithium transition metal composite oxide has the general formula Li a Ni x A y Co z M w O 2-b 3. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, represented by the formula: (wherein 0.95<a<1.05, 0.8≦x≦0.96, 0<y≦0.10, 0≦z≦0.15, 0≦w≦0.1, 0≦b<0.05, x+y+z+w=1, and M is at least one element selected from Mn, Fe, Ti, Si, Nb, Zr, Mo, and Zn).
4. The lithium transition metal composite oxide has a surface layer present from the surface to the inside, and a main body portion present on the inside side of the surface layer, 4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein a molar ratio of Al to Ni in the surface modification layer is greater than a molar ratio of Al to Ni in the main body portion when a composition analysis is performed by energy dispersive X-ray spectroscopy (TEM-EDX).
5. 5. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 4, wherein a molar ratio of Al to Ni in the surface modification layer is at least twice as high as a molar ratio of Al to Ni in the main body portion when a composition analysis is performed by energy dispersive X-ray spectroscopy (TEM-EDX).
6. 6. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the content of Ca relative to the total number of moles of metal elements excluding Li in the surface modification layer when a composition analysis is performed by energy dispersive X-ray spectroscopy (TEM-EDX) is 1.5 mol % to 20 mol %.
7. 7. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the content of Ni relative to the total number of moles of metal elements excluding Li in the lithium transition metal composite oxide is 90 mol % or more.
8. 8. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein no peak derived from CaO is present in an X-ray diffraction pattern obtained by X-ray diffraction measurement of the lithium transition metal composite oxide including the surface modification layer.
9. A non-aqueous electrolyte secondary battery comprising a positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 8, a negative electrode, and a non-aqueous electrolyte.
Citation Information
Patent Citations
Method for coating nickel cobalt lithium manganate positive-electrode material with calcium fluophosphate
CN103367723A
Y-doped CaMnO3 coated ternary positive electrode material and preparation method thereof
CN108682842A
Calcium fluoride coated lithium nickel manganate and preparation method thereof
CN109065868A
Positive active material for lithium secondary battery
JP2001291518A
Cathode activator for nonaqueous lithium secondary battery, manufacturing method of the same, and nonaqueous lithium secondary battery using the cathode activator
JP2005310744A